A Comparison of Mishrif Formation Characteristics in Kumait and Dujaila Oil Fields, Southern Iraq, Using Seismic Inversion Method and Petrophysical Properties Analysis - Al-Banna, Ahmed S.; Nassir, Nowfal A.; Al-Sharaa, Ghazi H. (Iraqi Journal of Science, 2020)
A comparison was conducted between two wells, Kt-1and Kt-2, in Kumait and two wells, Du-1and Du-2, in Dujaila oil fields that belong to Mishrif formation, southern Iraq. Seismic inversion method was employed to detect oil and water reservoirs. The comparison included the behavior of acoustic impedance (AI) of fluids and the lithology with related petrophysical properties. The values of water saturation, Shale volume (Vsh), and effective porosity were compared between the AI, two fluid reservoirs. It was found that the AI value for the oil reservoir unit is relatively low to medium, whereas it was relatively medium for the water reservoir. Effective porosity value showed, in general, an increase in the oil reservoir and a slightly decrease in the water reservoir. The Vsh and water saturation (Sw) values of the oil reservoir unit were in general lower than those in the water reservoir, which indicates the presence of hydrocarbons accumulation. The lithology and porosity are the main factors affecting the acoustic impedance values. Despite the small difference in density between oil and water, these two fluids still show perceptible variation in their properties.